FAKTOR YANG BERKONTRIBUSI TERHADAP KEPATUHAN PENGOBATAN TUBERKULOSIS (TB) PARU DI PUSKESMAS BANTARGADUNG SUKABUMI TAHUN 2022 - Dede Kerismon (2022)
Tuberculosis is a disease that is a public health problem both in Indonesia and the world so that it becomes one of the goals of sustainable health development. These bacteria attack the lungs and other organs such as the kidneys, spine and brain. This study aims to determine the factors that contribute to adherence to pulmonary tuberculosis (TB) treatment at the Bantargadung Public Health Center, Sukabumi. This study uses a quantitative method with cross-sectional. The use of the sample using the Lemeshow formula and sampling taken using a total sampling technique as many as 84 respondents using a questionnaire as a research instrument. Data analysis using chi-square test. The results of this study indicate that there is no relationship between age (p-value = 0.452), gender (p-value = 0.653), education (p-value = 0.356) and occupation (p-value = 0.624) and PMO (p-value = 0.624). value = 0.393) with pulmonary TB treatment adherence. Meanwhile, there is a relationship between knowledge and adherence to pulmonary TB treatment (pvalue = 0.000). Thus, from these results it can be concluded that age, gender, education, occupation and PMO have no relationship with pulmonary TB treatment adherence. Meanwhile, knowledge has a relationship with pulmonary TB treatment adherence. Future researchers are expected to develop mixed-method research methods so that the results obtained can be extracted from respondents regarding adherence to pulmonary TB treatment.